2014
DOI: 10.1254/jphs.13276fp
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor Effect of Polysaccharides From Scutellaria Barbata D. Don on the 95-D Xenograft Model via Inhibition of the C-Met Pathway

Abstract: Abstract. Polysaccharides isolated from Scutellaria barbata (PSB) have been reported to have anti-tumor effects. To investigate the underlying mechanism, a highly invasive, metastatic and phospho-c-Met overexpression lung carcinoma cell, 95-D cell line was used. The results showed that in vitro, PSB not only could inhibit the proliferation of 95-D cell line (IC 50 = 35.2 mg/mL), but also down-regulated the expression of phospho-c-Met and its downstream signaling molecules including phospho-Erk and phospho-Akt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
(24 reference statements)
0
23
0
Order By: Relevance
“…Modern pharmacological studies have showed that S. barbata (SB) has a wide variety of medical applications due to its antioxidant, anticancer, as well as anti-angiogenic effects, etc. [2][3][4]. Phytochemistry research found that flavonoids constituents, such as scutellarin, naringenin, apigenin, luteolin and wogonin, are the main effective components of SB [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies have showed that S. barbata (SB) has a wide variety of medical applications due to its antioxidant, anticancer, as well as anti-angiogenic effects, etc. [2][3][4]. Phytochemistry research found that flavonoids constituents, such as scutellarin, naringenin, apigenin, luteolin and wogonin, are the main effective components of SB [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…One of Traditional Chinese medicines (TCMs), Scutellariabarbata D. Don extraction (SBE) have been being applied independently or combined with modern medicine to improve symptoms, enhance quality of life, prevent recurrence and metastasis, and prolong survival in cancer patients in China for many years 21, 22, 25, 33, 34 . In our studies, SBE significantly inhibited the in vitro growth of human non-small cell lung cancer A549 and H1299 cells in dose-dependent manners.…”
Section: Discussionmentioning
confidence: 99%
“…Scutellariabarbata D. Don extraction (SBE), as one of TCMs, has been being used in China for many years as an efficacious anti-cancer drug 2225 . SBE is reported recently to induce cancer cell apoptosis by activating the mitochondrion-dependent pathway, to repress tumor angiogenesis via suppression of Hedgehog signaling, and to enhance G1/S arrest in human colon carcinoma cells by modulating a number of signaling pathways associated with the cell cycle 22, 2628 .…”
Section: Introductionmentioning
confidence: 99%
“…However, increased efficacy against lung cancers was noted by P3 because S. barbata is thought to have affinity for the lung meridian. Several recent laboratory studies on lung cancer have identified notable anticancer effects on a variety of lung cancer cell lines (Yang et al, 2015;Shiau et al, 2014;Yang et al, 2014;Gong et al, 2015). One Western study noted that S. barbata extract had greater than 50% inhibition for human lung carcinoma (A549), but also found that S. barbata was more effective against human breast adenocarcinoma (MCF-7) (Shoemaker et al, 2005).…”
Section: Comparison Of Current S Barbata Research With Traditional Tmentioning
confidence: 99%